PENERAPAN MODEL GAME BASED LEARNING (GBL) MENGGUNAKAN OODLU PADA MATERI GEJALA PEMANASAN GLOBAL DALAM MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA KELAS X SMA NEGERI 1 TANAH PUTIH - Aninda Nadya Tasya; Mitri Irianti; Ernidawati Ernidawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This study was carried out with the aim of determining cognitive learningoutcomes of students who apply the Game Based Learning (GBL) learning model usingoodlu, especially in the learning material of Global Warming Symptoms in class X SMA.Quasi-experimentation is a type of research used with the Posstest Only NonequvalentControl Group Design design. The population used was all students of class X SMA Negeri1 Tanah Putih as many as 150 people, with research samples, namely class X1 as a controlclass and class X5 as an experimental class. The instrument used to collect data is acognitive learning outcome test of class X students on Global Warming symptom materialwhich is then analyzed descriptively and inferentially. This study showed the results thatthe cognitive learning outcomes of students between the two classes had differences, wherestudents who were in the experimental class obtained higher cognitive learning outcomescompared to students in the control class, and also obtained the results that the GameBased Learning (GBL) learning model using oodlu was effectively used in improving thecognitive learning outcomes of class X SMA Negeri 1 Tanah Putih students on the materialSymptoms of Global Warming.Keywords: Game Based Learning Model, Oodlu, Cognitive Learning Outcomes, Symptoms ofGlobal Warming.